REPRESENTASI KUASA RAMALAN: PANGERAN DIPENOGORO DAN AKHIR TATANAN LAMA DI JAWA 1785-1855 KARYA PETER CAREY DALAM AKU DIPENOGORO! OLEH LANDUNG SIMATUPANG - Nur Alifah, Septiani (IdeBahasa, 2021)
Literary works are never separated from previous works or other texts. “Aku Dipenogoro!” is a literary work in the form of a drama script written by Landung Simatupang which was inspired by the power of divination by Peter Carey. The process of forming a literary work based on the acceptance of the past works can be said to be a reception. Therefore, this study used a reception approach to see how far the acceptance of previous works in Aku Dipenogoro!. The method used in this study is descriptive qualitative. In this case, the researcher compares the texts by looking at the similarities and differences. Furthermore, the findings are described. Based on the results of the analysis conducted by Aku Dipenogoro! as a literary work made several changes from the previous work (Peter Carey's Power of Prediction). These changes are used to give a dramatic effect in the work. Improvisation is used to get certain effects and aesthetics in a work. As a drama script Aku Dipenogoro! refers to dramatic effects in the performing arts (theater).